Towards Interactive Education: The Art of Scripting Mediated Activities - El Gazi, Safae; Ibrahimi, Ahmed (DIROSAT: Journal of Education, Social Sciences & Humanities, 2025)
This article explores how scripting mediated activities can transform traditional education into interactive and engaging education. The main objective is to analyze the impacts of this approach on student engagement and performance. The methodology adopted combines a qualitative study, based on semi-structured interviews with teachers, and a quantitative study, using questionnaires administered to students. The results show a significant increase in student engagement and an improvement in their academic performance in courses using well-scripted mediated activities. However, challenges remain, particularly in terms of teacher training and technological accessibility. The findings highlight the importance of scripting for effective integration of digital technologies in education and offer recommendations for successful implementation.